Analysis of the Consumer Market of Footwear at the "Uzbekcharmpoyabzal" Enterprises - Makhmudova, Dilfuza; Umarova, Makhfuza (European Journal of Life Safety and Stability (2660-9630), 2021)
This article analyzes marketing research in the footwear industry, which made it possible to draw a conclusion about the competitive advantages and disadvantages of footwear products that provide reliable and constant demand for domestic products.